Holes in the Safety Net? Social Security and the Alleviation of Poverty in a Comparative Perspective - Christina Behrendt (Luxembourg Income Study (LIS), 2000)
Although highly-developed welfare states in the industrialized world spend a large share of their income on social security, poverty and social exclusion have not been eradicated. The persistence of income poverty in industrialized welfare states casts serious doubt on the effectiveness of social security schemes in alleviating poverty. This paper explores the poverty-alleviating power of social security in a comparative perspective on the basis of house-hold micro-data from the Luxembourg Income Study. Do higher levels of social spending necessarily lead to a lower level of poverty, or does the effectiveness of poverty alleviation rather depend on how the money is spent? Special emphasis is placed on minimum income schemes. Which institutional structures have proved to guarantee an effective alleviation of poverty, and which ones are rather ineffective in this respect? What can be learned for future reforms?
Keywords: 330; Sozialstaat; Armut; Öffentliche Sozialausgaben; Armutsbekämpfung; Deutschland; Großbritannien; Schweden